PENGARUH PENGANGGURAN DAN ANGKA HARAPAN HIDUP TERHADAP INDEKS PEMBANGUNAN MANUSIA DIMEDIASI OLEH KEMISKINAN DI PROVINSI ACEH - M Hibatullah Huwaidi (AL-MUJADDID - JURNAL EKONOMI DAN BISNIS ISLAM, 2025)
This study aims to determine the influence exerted by active reactions and life expectancy on the human development index (HDI) in the province of Aceh. This study also includes poverty as an intervening variable. The method used is multiple regression analysis with secondary data from 2027-2021 obtained from the Central Bureau of Statistics for Aceh Province with SPSS 22 software. The results of this study indicate that HDI is significantly affected by life expectancy. Meanwhile, unemployment has a significant effect on poverty as an intermediary variable, although poverty itself does not have a significant effect on HDI.